2016
DOI: 10.1515/ngoe-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Spiritual Intelligence and Work Satisfaction among Leaders and Employees

Abstract: This study aims to investigate the relationship between spiritual intelligence and work satisfaction among both leaders and employees. Most studies in this area have focused on researching the relationship between employees' spiritual intelligence and work satisfaction, so we also researched the relationship between leaders' spiritual intelligence and work satisfaction. Our leading thesis was that leaders and employees with a higher level of spiritual intelligence have a higher level of work satisfaction. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
2
17
1
Order By: Relevance
“…From the statistical regression test, the findingis that the ISI cannot directly influence the emotional wellbeing. thus the insignificant result of ISI effect on EWB is support the research that counducted by several previous researchers (Ayranci & Semercioz, 2011;Koohbanani et al, 2013;Koražija et al, 2016) who found that spiritual intelligence is not always a strong predictor for workplace well-being. this result also supported by McCormack et al,(2014) with his finding that religion in organizational settings is not always inherently associated with positive organizational outcomes.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…From the statistical regression test, the findingis that the ISI cannot directly influence the emotional wellbeing. thus the insignificant result of ISI effect on EWB is support the research that counducted by several previous researchers (Ayranci & Semercioz, 2011;Koohbanani et al, 2013;Koražija et al, 2016) who found that spiritual intelligence is not always a strong predictor for workplace well-being. this result also supported by McCormack et al,(2014) with his finding that religion in organizational settings is not always inherently associated with positive organizational outcomes.…”
Section: Resultssupporting
confidence: 85%
“…Previous research measure the effect of individual spiritual intelligence toward individual wellbeing in the workplace. The increasing quality of spiritual intelligence will increase the higher level of engagement, working performance, employee satisfaction and decrease job burnout (Anbugeetha, 2015;Koražija et al, 2016;Roberts, 2013;Jeloudar& Goodarzi, 2012). But several research also reveal that spiritual intelligence is not significantly influence the job satisfaction (Koohbanani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dastjerdi et al ( 2013 ) researched 123 gifted females and ascertained no meaningful correlation between SI and satisfaction, but they did find that emotional intelligence was related to satisfaction. In the workplace setting, Koražija et al ( 2016 ) found no significant relationship between SI and work satisfaction for leaders, but they did find a significant, positive relationship between SI and workplace satisfaction for employees ( N = 200).…”
Section: Si In Relation To Well-beingmentioning
confidence: 94%
“…A study says that spiritual intelligence can benefit us because spiritual intelligence can be used in crisis problems which make us seem to lose our self-order. Still, with spiritual intelligence, our conscience will lead to a more righteous path (Koražija, Žižek, & Mumel, 2016). Furthermore, spiritual intelligence will be better if it is accompanied by good emotional intelligence because emotional intelligence is the ability to interpret, understand and manage the emotions of oneself and the people around them (Petrides et al, 2016), if spiritual intelligence and emotional intelligence can be well balanced, an individual will have self-regulating selfawareness, motivation.…”
Section: Introductionmentioning
confidence: 99%